Community based risk spectrum analysis in Uganda: Male and female livelihood risks and barriers to uptake of drought tolerant maize varieties - Mastenbroek, Astrid; Gumucio, Tatiana; Nakanwagi, Josephine; Kawuma, Christine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Even though drought tolerant maize (DTM) varieties have proven yield stabilization benefits, the adoptions remains low. In this research, we explore the risk spectrum that male and female smallholder farmers face in agriculture and the gendered barriers and drivers to adoption of drought tolerant maize varieties. The study appraises how communities in four district in Uganda are responding to observed changes and managing agricultural risks. The study uses exploratory qualitative research methods including participatory rural appraisal tools and focus group discussions with men’s and women’s groups separately. We observed that in Dokolo, but also in Iganga and Masindi districts, households operate in relative isolation, which on the one hand, harnesses them against risks but on the other hand makes them more vulnerable for the negative effects of personal risk, production risks, price risk and general poverty. Secondly, we observed that women can have less agency in comparison to men in that they have less land control and voice in agricultural decision- making processes; consequently, women can be more vulnerable to agricultural risk compared to men, in this respect. We elicited that many households optimize labor in the portfolio of different income generating activities to spread risk and smooth income and production. In Dokolo, Iganga and Masindi districts, we identified that health risk, production risk, (grain) price risk and financial risk (general poverty) are the most urgent risks that affect households productive choices. Narrowing down to DTM adoption, we noted that motivation (affordability considerations) combined with capability (knowledge on yield performance) constitute the largest barrier to adoption in all districts. In Dokolo we note capacity (knowledge of varieties) and opportunity (access to agro-dealers) as additional barriers. We also observed that due to low(ering) soil fertility, uptake of hybrid DTM should go together with fertilizer. Lastly we observed that these barriers may be more significant for women than for men. Further research should focus on the interplay of these four findings.